Kepuasan Kerja dan Komitmen Terhadap Organisasi - Raja Aziz, Raja Abdul Rashid (2006)
This research was aimed to identify job satisfaction and organizational commitment among the security guards of Security Unit, Prime Minister's Department (JPM). The research focused on the differences, relationships and influences of job satisfaction towards organizational commitment among the respondent. The variables used in this research are the dimensions of job satisfaction such as work situation, promotion, work environment, pays, peers, and supervision. This research was conducted using questionnaires of Job Description Index (JDI) developed by Smith et. al. (1969) and the Organizational Commitment Questionnaires (OCQ) developed by Mowday et. a1 . (1979). About 115 respondents was involved in this research, selected through sample random sampling. The data collected were analyzed and tested using statistical descriptives and inferences using t-Test, One Way ANOVA, Pearson Correlation, and Linear Regression. The findings indicated that the job satisfaction have a strong positive significant relation with the organizational commitment. The findings also indicated that intrinsic satisfaction had stronger influence than extrinsic satisfaction among the respondent. There are no significant differences of demographical aspect in relation to organizational commitment among the respondent. Based on the research findings, recommendations for the enhancement and improvement of job satisfaction in relation to organizational commitment of the security guards personnel will be forwarded for the consideration of Prime Minister's Department higher authority.